ALERTING REACTION IN OFFICE BLOOD PRESSURE AND TARGET ORGAN DAMAGE: AN INNOCENT PHENOMENON?. (September 2017) - Aparicio, L.; Barochiner, J.; Alfie, J.; Cuffaro, P.; Marin, M.; Morales, M.; Rada, M.; Waisman, G.
Abstract : Objective: An alerting reaction (AR) in office blood pressure (BP) is a physician-induced phenomenon which produces a transient BP rise. We determined the relationship between AR and target organ damage (TOD) in treated hypertensives. Design and method: We measured Office BP thrice with 1-minute intervals (Omron 7200). We measured glomerular filtration rate (GFR) through the MDRD formula, left ventricular mass index (LVMI, g/m 2 ) through modified Devereux's formula and carotid-femoral pulse wave velocity (PWV, m/s). We used three different AR calculations depending on the first, second or third office BP measurement: a) AR1 = BP1-BP3; b) AR2 = BP1-(mean BP2 and BP3); and c) AR3 = (mean BP1 and BP2)-BP3. We correlated these indexes with TOD (GFR, LVMI and PWV) and, for multivariate analysis, selected the AR index which better correlated with each TOD subtype. Results: We included 174 adults, mean age 67 (±13.7) years, 37.9% men, 4.6% smokers, 9.2% diabetics and 23.6% with a history of cardio-cerebrovascular event. Mean office BP was 141.2 (±17.1)/77.7 (±9.4) mmHg, heart rate was 70.5 (±11.8) bpm and average number of antihypertensives was 2.3 (±1.1). In general, office BP measurements dropped successively for all three AR indexes: 7.2 (±8.6)/1.9 (±4.7) mmHg for AR1; 5.9 (±7.9)/1.7 (±4) mmHg for AR2 and 4.9 (±6.4)/1.1 (±3.7) mmHg for AR3, with 75% of the patients having some degree of BP fall between measurements 1 to 3. Mean LVMI, GFR and PWV were 96.4 (±22.4) g/m 2, 81 (±19.3) mL/min/1.73 m 2, and 9.3 (±2.4) m/s, respectively. The systolic AR index which better correlated with LVMI was AR2: r = 0.20, p = 0.01 and with GFR was AR3: r = −0.17, p = 0.02. No correlations were significant for PWV nor diastolic AR. In multivariate linear regression models, after adjusting for classic risk factors, systolic AR2 and AR3 showed an independent association with LVMI and GFR, respectively. After further adjusting for office BP and white coat effect (calculated with standardized home BP monitoring, Omron 705CP), only GFR lost statistical significance (Table 1). Conclusions: Higher office AR is related to increased TOD in treated hypertensives. Figure. No caption available.